A study on occupational stress and work commitment of teachers taking up long-distance learning in Kuching, Sarawak / Samen Anak Sanggod @ Sanggon - Sanggod @ Sanggon, Samen (2009)
The purpose of this study was firstly, to investigate the level of occupational stress and work commitment of teachers taking up long-distance learning in Kuching, Sarawak. Secondly, to rank the occupational stress domains they experienced and finally, to determine the relationships between the occupational stress and work commitment. The samples comprised 121 TESL teachers conveniently selected from Open University Malaysia, Sarawak. The five domains of occupational stress were identified and discussed. The relationship between occupational stress domain and demographic information such as gender, marital status, school level, school location and years of teaching experience were studied. Frequency and correlation analyses were utilized to investigate the hypothesized relationship. Findings indicated that majority teachers were very stressful and the main stressor was the external domain. This was later followed by the time, student, school and personal domains. The findings revealed a significant relationship between occupational stress and work commitment of teachers taking up long-distance learning. However, there was no strong significant relationship between occupational and demographic variables. Therefore, it was concluded that causes of stress among teachers were the result of constant changes in the education system and the demand by the Ministry of Education. The study also implied that the more committed the teachers to their work, the more stressful they would become. The overall results of the finding showed that teachers doing long-distance learning were moderately stressful but preferred to be committed to their work.